2021
DOI: 10.3390/biom11081222
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Sambucus nigra L. Flowers Aqueous Extract and Its Biological Implications

Abstract: The main goal of this study was to chemically characterize an aqueous S. nigra flower extract and validate it as a bioactive agent. The elderflower aqueous extraction was performed at different temperatures (50, 70 and 90 °C). The extract obtained at 90 °C exhibited the highest phenolic content and antiradical activity. Therefore, this extract was analyzed by GC-MS and HPLC-MS, which allowed the identification of 46 compounds, being quercetin and chlorogenic acid derivatives representative of 86% of the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 93 publications
1
18
0
Order By: Relevance
“…This extract is composed mostly of quinic acid, p-coumaroyl-caffeoylquinic, coumaroylquinic, caffeoylquinic, and feruloylquinic acids, quercetin, isorhamnetin, quercetin-3-rutinoside, kaempferol and naringenin (data obtained by HPLC-MS). 17 Other authors have also reported a similar phenolic profile of aqueous S. nigra flower extracts. 5,34 In S. nigra berry extracts, the profile of phenolic compounds is simpler.…”
Section: Food and Function Papermentioning
confidence: 67%
See 1 more Smart Citation
“…This extract is composed mostly of quinic acid, p-coumaroyl-caffeoylquinic, coumaroylquinic, caffeoylquinic, and feruloylquinic acids, quercetin, isorhamnetin, quercetin-3-rutinoside, kaempferol and naringenin (data obtained by HPLC-MS). 17 Other authors have also reported a similar phenolic profile of aqueous S. nigra flower extracts. 5,34 In S. nigra berry extracts, the profile of phenolic compounds is simpler.…”
Section: Food and Function Papermentioning
confidence: 67%
“…The extraction of bioactive compounds from the flowers and berries of S. nigra was carried out by the method described by Ferreira-Santos et al 17 Briefly, 5 g of dry material was placed in a cylindrical reactor of 250 mL capacity with 150 mL of distilled water in a thermostatic water bath with agitation (130 rpm) at a temperature of 90 °C for 30 min. The reaction was duly protected from light.…”
Section: Extraction Conditions and Extract Preparationmentioning
confidence: 99%
“…Antimicrobial activity was also evaluated. The results were promising, showing the great potential of its bioactive compounds as nutraceuticals, pharmaceuticals and cosmetics for therapeutic purposes [31]. Other studies, such as those by Domínguez et al (2020), highlighted the antioxidant activity of the fruits of this species due to their phenolic-compound content.…”
Section: Resultsmentioning
confidence: 85%
“…The OD 600 of 100 μl of NB solution containing the same concentration of DMSO or compounds was measured for correction. The inhibition rate was calculated using the following formula (Ferreira-Santos et al, 2021 ):…”
Section: Methodsmentioning
confidence: 99%